Clamp bending machine and annealed wire cutter for reinforced concrete columns - Marron, J. (2020)
This study developed a reinforced steel rod bending machine for rods with diameters of up to 8 mm and annealed wire cutter for up to 5 kg for replacing manual intervention required to bend rods in reinforced concrete columns. This study aims to reduce the physical effort that could lead to occupational diseases, such as tenosynovitis, bursitis, muscle disorders. Clamp manufacturing possesses great risk for workers, who are exposed to injuries while using different cutting devices, such as grinders and electric saws. They also face potential problems such as muscular fatigue due to the nonergonomic and repetitive work positions. The proposed machine features a mechanical dragging and bending systems and manual shears. Additionally, the proposed machine has been designed theoretically and its effectiveness has been assessed through simulations conducted using the SolidWorks CAD software. A bending machine prototype for producing clamps is developed and its machine productivity is measured. Using this machine, approximately 300 clamps can be bent per hour without possessing any risk to the worker.